Analytical development for the assessment of pesticide contaminations in blood and plasma of wild birds: The case of grey partridges (Perdix perdix) - Rodrigues, A; Gaffard, A; Moreau, J; Monceau, K; Delhomme, O; Millet, M (Journal of Chromatography A, 2023)
•Methods allowed sensitive detection and quantification of pesticides in birds.•Blood and plasma from grey partridges were appropriated matrices for biomonitoring.•Analyses of both matrices allowed a good assessment of environmental contaminations.•Blood allowed higher levels of detection with easier sampling than plasma. In this study, blood and plasma of grey partridges (Perdix perdix) were analyzed to assess their potential contamination by plant protection products (PPP) and especially pesticide compounds. The group of pesticides selected is composed of a huge variety of compounds. Therefore, in this study, two methods were optimized and validated to analyze 104 compounds including herbicides, insecticides, fungicides and photoprotectors or synergists. Various extraction methods found in the literature were compared and adapted for the extraction of pesticides from blood and plasma. After extraction, samples were concentrated then injected for quantification simultaneously in LC-MS/MS and ATD-GC-MS/MS with an automatic thermal desorption step (ATD). Both LC-MS/MS and ATD-GC-MS/MS analyses were performed using the MRM mode with 2 mass transitions for each compound.The two analytical methods achieved a good linearity for the calibration responses in plasma and blood. Methods allowed sensitive detection and quantification in complex biological matrices such as plasma and blood in both LC and GC. For plasma samples and considering all 104 compounds of the study, the average LOD was 0.005 ng mg−1 in LC-MS/MS and 0.035 ng mg−1 in ATD-GC-MS/MS and the average LOQ was 0.017 ng mg−1 and 0.116 ng mg−1 in LC-MS/MS and ATD-GC-MS/MS respectively. Accordingly, the average LOD for blood samples was 0.011 ng mg−1 in LC and 0.028 ng mg−1 in GC whereas the average LOQ was 0.038 ng mg−1 and 0.094 ng mg−1 in LC-MS/MS and ATD-GC-MS/MS respectively. Those analytical methods were then successfully applied to 70 blood samples and 35 plasma samples.